Mapping of Murine Th1 Helper T-Cell Epitopes of Mycolyl Transferases Ag85A, Ag85B, and Ag85C from Mycobacterium tuberculosis - D'Souza, S. (American Society for Microbiology, 2003)
BALB/c (H-2(d)) and C57BL/6 (H-2(b)) mice were infected intravenously with Mycobacterium tuberculosis H37Rv or vaccinated intramuscularly with plasmid DNA encoding each of the three mycolyl transferases Ag85A, Ag85B, and Ag85C from M. tuberculosis. Th1-type spleen cell cytokine secretion of interleukin-2 (IL-2) and gamma interferon (IFN-γ) was analyzed in response to purified Ag85 components and synthetic overlapping peptides covering the three mature sequences. Tuberculosis-infected C57BL/6 mice reacted strongly to some peptides from Ag85A and Ag85B but not from Ag85C, whereas tuberculosis-infected BALB/c mice reacted only to peptides from Ag85A. In contrast, spleen cells from both mouse strains produced elevated levels of IL-2 and IFN-γ following vaccination with Ag85A, Ag85B, and Ag85C DNA in response to peptides of the three Ag85 proteins, and the epitope repertoire was broader than in infected mice. Despite pronounced sequence homology, a number of immunodominant regions contained component specific epitopes. Thus, BALB/c mice vaccinated with all three Ag85 genes reacted against the same amino acid region, 101 to 120, that was also immunodominant for Ag85A in M. bovis BCG-vaccinated and tuberculosis-infected H-2(d) haplotype mice, but responses were completely component specific. In C57BL/6 mice, a cross-reactive T-cell response was detected against two carboxy-terminal peptides spanning amino acids 241 to 260 and 261 to 280 of Ag85A and Ag85B. These regions were not recognized at all in C57BL/6 mice vaccinated with Ag85C DNA. Our results underline the need for comparative analysis of all three Ag85 components in future vaccination studies.